Molecular phylogeny and morphological revision of the Ctenotus labillardieri (Reptilia: Squamata: Scincidae) species group and a new species of immediate conservation concern in the southwestern Australian biodiversity hotspot - Kay, Geoffrey M.; Keogh, J. Scott (Zootaxa, 2012)
Ctenotus is the largest and most diverse genus of skinks in Australia with at least 97 described species. We generated largemitochondrial and nuclear DNA data sets for 70 individuals representing all available species in the C. labillardieri species-group to produce the first comprehensive phylogeny for this clade. The widespread C. labillardieri was sampled extensively toprovide the first detailed phylogeographic data set for a reptile in the southwestern Australian biodiversity hotspot. Wesupplemented our molecular data with a comprehensive morphological dataset for the entire group, and together these data areused to revise the group and describe a new species. The morphologically highly variable species C. labillardieri comprisesseven well-supported genetic clades that each occupy distinct geographic regions. The phylogeographic patterns observed inthis taxon are consistent with studies of frogs, plants and invertebrates, adding strength to emerging biogeographic hypothesesin this iconic region. The species C. catenifer, C. youngsoni, and C. gemmula are well supported, and despite limited samplingboth C. catenifer and C. gemmula show substantial genetic structure. The threatened C. lancelini from Lancelin Island and theadjacent mainland is the sister taxon to a new species from the Swan Coastal Plain, which we describe as C. ora sp. nov. Thisspecies is a habitat specialist, occurring primarily in sandy regions south of Perth that currently are under intense development. Ctenotus ora sp. nov. should be considered for conservation attention immediately.